Evaluasi Kerusakan Lapisan Permukaan Jalan dengan Metode PCI dan Tindakan Preservasi di Jalan Pemda, Kapur, Kec.Sungai Raya, Kab.Kubu Raya - Aprilia Putri Santoso; Eti Sulandari; Siti Mayuni (Pusat riset dan Inovasi Nasional, 2026)
Pemda Road in Kapur Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan is a district road that functions as an alternative route connecting Tanjung Raya II Road and Kapur Village Main Road. Along with increasing traffic loads and limited maintenance, this road section has experienced various surface pavement distresses that reduce driving comfort and compromise road safety. This paper seeks to detect the types and severity levels of pavement damage and to determine appropriate preservation actions using the Pavement Condition Index (PCI) method. The research method involved a visual field survey by dividing the road into several segments, identifying damage types and severity levels, calculating PCI values, and determining suitable preservation measures based on the Asphalt Institute MS-17 guidelines. The results indicate that the flexible pavement section has a PCI value of 21.643, classified as very poor, with dominant damages consisting of potholes and edge cracking. Meanwhile, the rigid pavement section shows a PCI value of 94.960, which falls into the excellent category. The results of this research are anticipated to facilitate decision-making in determining maintenance priorities and road preservation strategies to improve pavement performance and extend service life.